Perceptions of the harm, addictiveness, and smoking cessation effectiveness of e-cigarettes among Australian young adults - Jongenelis, Michelle; Kameron, C.; Rudaizky, D.; Slevin, Terry; Pettigrew, Simone (Pergamon, 2019)
© 2018 Elsevier Ltd An extensive body of evidence indicates that e-cigarette use is highest among young adults, prompting concerns about the potential renormalization of smoking behaviors in a population segment that is particularly vulnerable to tobacco smoking initiation. Increasing levels of e-cigarette use among young adults are likely a reflection of favorable beliefs about the benefits and risks associated with use, but research assessing perceptions of e-cigarettes in this population segment is limited. The aim of the present study was to assess young adults' perceptions of (i) the absolute and relative harm associated with e-cigarette use and (ii) the efficacy of these devices for smoking cessation. In a sample of 1116 Australian 18 to 25 year olds, three-quarters believed e-cigarettes have some level of harm (72%), just over half believed them to be addictive (57%), and substantial minorities reported that they did not know whether these products are harmful (20%) or addictive (34%). Two-fifths believed e-cigarettes are effective at helping people quit smoking (42%). Differences were observed by smoking status and e-cigarette user status on several variables, with a general trend of more positive perceptions towards e-cigarettes among smokers and users, particularly in relation to cessation efficacy. Results suggest that a substantial minority of young adults are unaware of the harms that may be associated with e-cigarettes, underscoring the importance of public health efforts that aim to provide accurate information about these devices.